Comments on "Bayesian Update and Method of Distributions: Application to Leak Detection in Transmission Mains" by Alawadhi and Tartakovsky. Issue 9 (18th September 2020) - Wang, Xun; Che, Tong‐Chuan; Ghidaoui, Mohamed S.
Abstract: In a recent paper (Alawadhi & Tartakovsky, 2020, https://doi.org/10.1029/2019WR025879 ), Alawadhi and Tartakovsky proposed an interesting, novel, efficient, and potentially powerful Bayesian‐based approach to cope with the uncertainty in initial flow velocity when using transient waves to detect leaks in pressurized pipes. In this discussion, we illustrate that the uncertainty in initial flow velocity has negligible effect on the accuracy of transient‐based leak detection methods. On the other hand, uncertainties in the wave speed have significant effects on the leak detection accuracy. Unfortunately, it appears that the proposed approach cannot be easily, if at all, extended to deal with uncertainties in wave speed and one may have to resort to classical Bayesian approaches which could be computationally intensive. Key Points: We illustrate that the uncertainty in initial flow velocity has negligible effect on leak detection We illustrate that the uncertainty in wave speed has significant influence on leak detection We use the sensitivity analysis and the MFP method to justify the importance of uncertainty parameters